Starch to protein ratio and α-amylase activities in grains of different wheat cultivars - Csiszár, Jolán (Acta Biologica Szegediensis, 2010)
Starch and total protein contents, α-amylase activity of grains as well as falling number in the flour, an internationally accepted measure of α-amylase activity in the food industry, were compared in wheat (Triticum aestivum L.) genotypes which are widely used in the agriculture and breeding in Romania and Hungary. These cultivars were originated from Romania (20 cultivars), Hungary (cv. GK Élet, GK Öthalom and Mv Emese), France (cv. Cappelle Desprez), the USA (cv. Plainsman) and China (cv. Xiang). The starch contents of the grains were high in those cultivars, where the protein contents were relatively low. The highest starch content among the investigated wheat genotypes was found in the Romanian Gruia cultivar, which could be characterized also with low starch degrading α-amylase activity in the grain and with a high falling number. This wheat genotype can be a good candidate for utilization in starch industry. Other genotypes, which had relatively high starch contents and, a low α-amylase activity (or high falling number) were the Romanian Crina and Gloria, the Hungarian GK Öthalom, GK Élet, Mv Emese and the French Cappelle Desprez cultivars.